AN ANALYSIS OF SENTENCE PROBLEMS IN STUDENTS’ WRITINGS OF RECOUNT TEXTS - Apriliana Sasnila Damayanti (Universitas Pesantren Tinggi Darul Ulum Jombang (Unipdu), 2022)
Sentence problems often occur when students write stories in English such as recount text. There are several types of sentence errors that occur and must be avoided by students. The purpose of this study is (1) to find types of sentence problems the students' writing in recount text. 2) describing and explaining the problems that occurred, and the subject of this study was a class 10 student at MA, Darul Ulum Jombang. This study uses descriptive qualitative analysis to analyze students' writing errors proposed by the theory of Oshima and Hogue (1981). Based on this analysis, it has been found that there are 3 types of sentence errors made by students in writing recount text. The results of this study indicate that the more dominant error made by superior MA students from Darul Ulum Jombang is choppy sentences as many as 6 students, because they repeat the same subject too often in one sentence, and also excrete based on equel and unequel ideas. The second error is stringy sentences, students use too many connecting words that are connected to independent clauses in one sentence. and the smallest error is sentence fragment with 3 total student errors. this needs to be avoided in the process of learning to write recount text.